PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS WEB MELALUI GOOGLE SITES PADA PEMBELAJARAN IPAS DI KELAS IV SEKOLAH DASAR - Pradika Alim Zulemil; Fikhen Tri Wulandari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research develops interactive web-based learning media using Google Sites for the Natural and Social Sciences (IPAS) subject in grade IV elementary schools to support the implementation of the Kurikulum Merdeka. The research employed a Research and Development (R&D) method with the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. Learning needs were identified through observation, interviews, and questionnaires in six elementary schools in Padang. The media was designed with visual displays, audiovisual elements, and interactive quizzes. Expert validation of content, language, and media reached an average of 94% (very valid). Practicality tests in three schools, involving teachers and students, achieved averages of 93.3% and 90.9% (very practical). Effectiveness testing using the N-Gain formula yielded an average score of 0.51 (moderately effective) and increased student mastery from 32–39% to 82–91%. These results confirm that Google Sites–based media effectively enhances students’ understanding and engagement, making it a feasible and innovative alternative for IPAS learning in the Kurikulum Merdeka framework.